Comparison of the TIP4P-2005, SWM4-DP and BK3 interaction potentials of liquid water with respect to their consistency with neutron and X-ray diffraction data of pure water - Steinczinger, Z.; Pusztai, L. (Condensed Matter Physics, 2013)
Following a fairly comprehensive study on popular interaction potentials of water (Pusztai et al 2008, J. Chem. Phys., 129, 184103), here two more recent, polarizable potential sets, SWM4-DP (Lamoureux et al., Chem. Phys. Lett., 2006, 418, 245) and BK3 (Kiss et al. J. Chem. Phys., 2013, 138, 204507) are compared to the TIP4P-2005 water potential (Abascal et al., J. Chem. Phys., 2005, 123, 234505) that had appeared the most favoravble previously. The basis of comparison was the compatibility with results of neutron and X-ray diffraction experiments on pure water, using the scheme applied by Pusztai et al. (2008). The scheme combines the experimental total scattering structure factors (TSSF) and partial radial distribution functions (PRDF) from molecular dynamics simulations in a single structural model. Goodness-of-fit values to the O-O, O-H and H-H simulated PRDF-s and to the experimental neutron and X-ray TSSF provided a measure that can characterize the level of consistency between interaction potentials and diffraction experiments. Among the sets of partial RDF-s investigated here, the ones corresponding to the SWM4-DP potential parameters have proven to be the most consistent with the particular diffraction results taken for the present study, by a hardly significant margin ahead of BK3. Perhaps more importantly, it is shown that the three sets of potential parameters produce nearly equivalent PRDF-s that may all be made consistent with diffraction data at a very high level. The largest differences can be detected in terms of the O-O partial radial distribution function. Слiдуючи досить повному вивченню популярних потенцiалiв взаємодiї для води (Pusztai et al., J. Chem.
Phys., 2008, 129, 184103), у цiй роботi два бiльш сучасних потенцiали з врахуванням поляризованостi молекул типу SWM4-DP (Lamoureux et al., Chem. Phys. Lett., 2006, 418, 245) i BK3 (Kiss et al., J. Chem. Phys., 2013, 138, 204507) порiвняно з моделлю TIP4P-2005 (Abascal et al., J. Chem. Phys., 2005, 123, 234505), яка донедавна вважалася найуспiшнiшою. Основою для порiвняння є узгодження з результатами експериментiв по розсiянню нейтронiв та рентгенiвського випромiнювання для чистої води, використовуючи процедуру, розроблену Пустаї та iн. (2008). Ця процедера поєднує повнi структурнi фактори розсiяння i парцiальнi радiальнi функцiї розподiлу, що слiдують з молекулярної динамiки певної структурної моделi. Якiсть узгодження значень функцiй розподiлу O–O, O–H i H–H з моделювання пiсля їх перетворення до повних структурних факторiв i порiвняння з експериментальними факторами є мiрою для опису рiвня узгодження. Серед парцiальних функцiй розподiлу, дослiджених у цiй роботi, тi фактори, якi вiдповiдають моделi SWM4-DP виявилися найкращими, але лише незначно кращими вiд тих, що були отриманi з моделi BK3.
Важливо вiдзначити, що усi три потенцiали дають майже еквiвалентнi радiальнi функцiї розподiлу, якi узгоджуються з експериментом, але невелика розбiжнiсть спостерiгається для функцiй розподiлу киснiв O–O.